1991
DOI: 10.1002/jnr.490290115
|View full text |Cite
|
Sign up to set email alerts
|

Increased release of an amyloidogenic C‐terminal Alzheimer amyloid precursor protein fragment from stressed PC‐12 cells

Abstract: Amyloid plaques, found in characteristically large numbers in specific brain areas of Alzheimer's disease (AD) and Down's Syndrome (DS) patients, are composed of a 41-43 amino acid peptide, A4, derived from a transmembrane glycoprotein, amyloid precursor protein (APP). In transformed cells APP has been shown to be cleaved within the extracellular portion of the A4 region causing the release of 100-120 kDa soluble N-terminal APP products. If this cleavage occurs in human tissue, neither the soluble product nor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Anyhow, the presence in CSF of soluble forms of full-length membrane proteins containing the transmembrane and intracellular domains is not an unusual finding 16, 17 . Early studies failed to detect short C-terminal fragments of APP in the medium of cultured cells 18 ; but others suggested the release of largest APP-CTF fragments from cultured neural cells 19 . Moreover, a series of APP-CTFs was found to be secreted within exosomes in cultured cells 20 , as well AICD 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Anyhow, the presence in CSF of soluble forms of full-length membrane proteins containing the transmembrane and intracellular domains is not an unusual finding 16, 17 . Early studies failed to detect short C-terminal fragments of APP in the medium of cultured cells 18 ; but others suggested the release of largest APP-CTF fragments from cultured neural cells 19 . Moreover, a series of APP-CTFs was found to be secreted within exosomes in cultured cells 20 , as well AICD 21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in the transmembrane topology of APP, the peptide bond cleaved by ,y-secretase is located within the lipid bilayer and may not be easily accessible to proteases. It is therefore possible that A3 is derived from soluble nontransmembrane precursors where the peptide bond cleaved by y-secretase is not protected by the lipid bilayer (5,6 (6,(10)(11)(12). It has been suggested that the latter species are derived from solAPPcyt and may be further degraded to produce AP3 (6).…”
mentioning
confidence: 99%
“…Inhibition of the mid-A4 APP cleavage protease, secretase (Esch et al, 1990), may promote an alternative (Baskin et al, 1991;Golde et al, 1992) APP cleavage, yielding intact A4 peptides in AD and DS. Characterization of factors regulating secretase and of the cell types which express it will be important in understanding the pathological mechanisms causing AD and in choosing therapeutic agents which do not worsen this amyloid induced pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The 15 kDa C-terminal APP seen with C-terminal antisera C7 or Athena 6 is not precipitated with an antisera elicited by A4 residues 1-17 (Palmed et al, 1989), is produced in stoichiometric amounts with the release of protease nexin I1 (Anderson et al, 1991;Baskin et al, 1991;Oltersdorfet al, 1989), and is not seen if 5 pg/ml leupeptin (serine-protease inhibitor) is included in the chase buffer.…”
Section: Analyses Of App Processing and Cleavage In Pc-12 Cellsmentioning
confidence: 99%